PERBEDAAN TINGKAT DEPRESI ANTARA LANSIA DI PEDESAAN DAN PERKOTAAN - Tunjung Sri Yulianti; Anggit Ike Prascika (Sekolah Tinggi Ilmu Kesehatan Panti Kosala, 2016)
AbstractElderly will fail maintaining a balance of physiological conditions, thereby increasingvulnerability to depression. Factors that influence is the socio-economic changes, socialvalues, awareness among individuals and others. More urban environment isindividualistic and socioeconomic pressures are higher, while rural areas have theeducational background lower. The results showed not a few elderly people who returnedto the village because they felt pressured by the situation in the city, the elderly should bealone in the house and no neighbors who could be invited to communicate, so it isdifficult to be happy. But there are also elderly who live in the village reveal feelingdepressed and showed signs of depression. Purpose of the study to determine the levelof depression in the elderly in urban, rural and differences in the level of depressionamong the elderly who live in rural and urban areas.Subjects were elderly who live in the village of Palur Sukoharjo and Kampung SewuSurakarta. Methods of analytical study comparative research design. Measuringinstrument used is the Geriatric Depression Scale. Test data normality using theKolmogorov-Smirnov Test. Statistical test with independent t test.The results of the study obtained significancy value of t-test (two-tailed) 0.001.Conclusion of research is significant difference in rates of depression among the elderlyin urban and rural areas, the elderly in urban areas have higher levels of depression thanelderly people in rural areasKeywords: Elderly Depression Level, Rural, Urban